Socioeconomic determinants of excess weight and central obesity among Iranian women: Application of information, motivation, and behavioral skills model - Maryam Mohammadi-Nasrabadi; Roya Sadeghi; Abbas Rahimiforushani; Fatemeh Mohammadi-Nasrabadi; Davoud Shojaeizadeh; Ali Montazeri (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: In developing countries, there is an increased risk of incidence of noncommunicable diseases due to general and abdominal obesity. Therefore, this study aimed to assess socioeconomic determinants of excess weight and central obesity among women in Tehran city based on information motivation behavioral skills model (IMB). MATERIALS AND METHODS: A cross-sectional study was conducted among 260 women aged between 20 and 49 years old using cluster sampling. A skilled interviewer completed socioeconomic status (SES), food insecurity, and IMB questionnaires. Analysis of variance, Chi-square tests, and regression model were used for statistical analysis. The multiple logistic regression analysis was used to identify independent predictors of the excess weight and central obesity using SPSS 21. RESULTS: The mean and standard deviation of participants' age was 34.7 (±7.59) years old. The prevalence of overweight and obesity in adult women was estimated 35% and 21.2%, respectively. The prevalence of abdominal obesity was 34.6%. Independent predictors of overweight/obesity in women were age (odds ratio [OR] =1.09, 95% confidence interval [CI] =1.03-1.14), educational level (OR = 2.35, 95% CI = 1.05-5.27), and total expenditure (OR = 3.14, 95% CI = 1.06-9.37). Whereas, independent predictors for increased the likelihood of central obesity were age (OR = 1.12, 95% CI = 1.06-1.18), marital status (OR = 6.44, 95% CI = 1.94-21.40), low education (OR = 0.38, 95% CI = 0.16-0.91), number of rooms (OR = 1.19, 95% CI 1.03-3.45), and self-regulation score (OR = 0.94, 95% CI = 0.88-1.00). CONCLUSIONS: The socioeconomic determinants, especially age, level of education, and expenditure, as well as self-regulation, play an important role in excess weight and central obesity among women. Therefore, further research is needed to reach women in different SES groups with a variety of interventions through concurrent triangulation of longitudinal studies and qualitative research.